Effectiveness of gait aid prescription for improving spatiotemporal gait parameters and associated outcomes in community-dwelling older people: a systematic review. Issue 21 (9th October 2022) - Lee, Den-Ching A.; Dissanayaka, Thusharika; Burton, Elissa; Meyer, Claudia; Hunter, Susan W.; Suttanon, Plaiwan; Ekegren, Christina L.; Stout, Julie C.; Dawes, Helen; Hill, Keith D.
Abstract: Purpose: To integrate the evidence of gait aid prescription for improving spatiotemporal gait parameters, balance, safety, adherence to gait aid use, and reducing falls in community-dwelling older people. Methods: Seven health databases were searched to June 2021. Experimental studies investigating gait aid prescription (provision and instruction for use) for older people, reporting gait parameters, balance, falls, and safety of or adherence to gait aid use was included. Mean differences with 95% confidence intervals of gait and balance outcomes in participants at the program's last follow-up were analyzed. The safety of and adherence to gait aid use were described. Results: Eight studies were included ( N  = 555 older people). No meta-analyses could be performed. Five studies used a single gait aid instruction session. Gait aid prescription had inconsistent effects on gait velocity, and no reported benefits in reducing gait variability in older people with mobility problems or fall risks, including Parkinson's or Alzheimer's disease. No study investigated gait aid prescription on falls and balance performance. Effects on safety and adherence to gait aid use were unclear. Conclusion: Research is needed to investigate the benefits of extensive gait aid training in older people with mobility problems, including those with dementia or high falls risk. IMPLICATIONS FOR REHABILITATION: There is little evidence currently addressing the benefits of gait aid prescription on gait and associated outcomes in older people with mobility problems or fall risks. Gait aid prescription yielded inconsistent effects on increasing gait velocity and did not appear to reduce gait variability in older people with mobility problems or fall risks, nor in those with Parkinson's disease or Alzheimer's disease. Clinicians may consider using a more extensive gait aid training approach to optimize learning of safe gait patterns and gait aid use, which may produce better outcomes.